First bride to fall - Baird, Ginny (Entangled Publishing, 2022)
Nell Delaney will do almost anything for her parents and her two sisters. But enter a marriage of convenience to save the family's coffee shop? Too far. So Nell and her sisters strike a deal: whoever hasn't found love in thirty days has to step up to take one for the team. The good news? Nell knows the perfect guy to fall in love with. The bad news? She's going to have to pretend she likes the outdoors ... a lot. Adventure guide Grant Williams knows immediately that Nell is not exactly Little Miss Outdoorsy. She's a walking natural disaster--an amazingly adorable disaster. And whoa, their chemistry is unbelievable. Everything between them is so perfect, he's not even a little bit shocked when he starts thinking of forever ... Right up until he catches the town gossiping about the Delaney sisters' bargain and realizes she's just using him to win a bet. Unfortunately, his family's unreliable reputation means he can't just dump one of the town's sweethearts. No, she needs to dump him. If she's going to pretend to be the perfect doting bride, well, he'll just pretend to be the worst bachelor on the market.